Angular spectrum symmetry for beam-path design in laser fusion facility. (17th October 2018) - Yang, Ying; Wang, Deen; Zhang, Xin; Yuan, Qiang; Deng, Xuewei; Hu, Dongxia; Wei, Xiaofeng; Zhang, Xiaomin; Li, Mingzhong; Wang, Wenyi; Li, Fuquan
Abstract: A novel beam-path design method for the laser fusion facility is proposed in this paper. The beam passes and reflectors are represented by their angular spectrum, and the multi-pass amplifier optical design is accomplished by symmetry operation which reflects the beam propagation. Theoretical analysis of the performance of this method shows that using this angular spectrum symmetry method, the directional error between the actually reflected beam and the calculated beam can be limited to 0.1 µ rad, which is smaller than the random error caused by vibrations and drifts.